Research Reviews on Electrical Contact Between Pantograph and Catenary of High-speed Railway - 陈立; 吴广宁; 高国强; 朱军; 王波 (机车电传动)
Domestic and oversea researches on mechanism of arc, arc energy loss, discipline of friction and wear with current and pantograph and catenary materials were discussed, and probable issues during studies and related researching direction were pointed out, which supplied a foundation for further researches on electrical contact between pantograph and catenary.